On conformally flat lorentzian spaces satisfying a certain condition on the curvature tensor - Erdo?an, M. (My University, 1996)
In this paper we prove a local classification theorem for the conformally flat lorentzian spaces satisfying the condition R(X, Y)R = 0. © TÜBÍTAK.
E?ri?li?k tensörü beli?rli? bi?r şarti sa?layan konformal flat lorentz uzaylari hakkinda